Influence of Ageing on Flexible Pavement Interface Bond under Repeated Shear Stresses - Saad Issa Sarsam; Samah Abdulrazzaq AL Nuaimi (Britain International for Academic Research (BIAR) Publisher, 2020)
The durability of interface bond was not sufficiently taken into consideration, and the research work in this field is scares and scattered. The interface bond usually practices dynamic shear stresses throughout its service life while ageing due to volatilization provide stiffness at the interface. In this investigation, an attempt has been made to assess the durability of the interface bond in terms of resistance to ageing under repeated shear stresses. Two types of tack coat (Rapid Curing cutback RC-70 and Cationic Medium setting emulsion CMS) and three application rates have been implemented in the preparation of two layers slab samples (base overlaid by binder, and binder overlaid by wearing) courses using roller compactor. Asphalt concrete core specimens were obtained from the roller compacted slab samples and subjected to long term ageing, then the specimens were subjected to 1200 repeated shear stress cycles. The accumulation of permanent deformation was monitored. Afterwards, the specimens were tested for interface shear strength at 20 °C. Control specimens were also tested for comparison. It was concluded that ageing reduces the total microstrain for RC-70 tack coat by (43.6, 25.6, and 29.5) % and (50, 51.3, and 30.2) % for (binder-base) and (wearing-binder) interfaces for the application rate of (0.15, 0.33, 0.5) l/m2 respectively. However, ageing reduces the total microstrain for CMS tack coat by (37, 35.5, and 40.3) % and (45.2 , 49, and 46.8) % for (binder-base) and (wearing-binder) interfaces for the application rate of (0.1, 0.23, 0.35) l/m2 respectively. Ageing increases the interface bond shear strength by a range of (8-27)% for various interfaces, tack coat type and application rates.